2022
DOI: 10.3389/fphar.2022.798053
|View full text |Cite
|
Sign up to set email alerts
|

Daprodustat Accelerates High Phosphate-Induced Calcification Through the Activation of HIF-1 Signaling

Abstract: Aims: Chronic kidney disease (CKD) is frequently associated with other chronic diseases including anemia. Daprodustat (DPD) is a prolyl hydroxylase inhibitor, a member of a family of those new generation drugs that increase erythropoiesis via activation of the hypoxia-inducible factor 1 (HIF-1) pathway. Previous studies showed that HIF-1 activation is ultimately linked to acceleration of vascular calcification. We aimed to investigate the effect of DPD on high phosphate-induced calcification.Methods and Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 47 publications
2
19
0
Order By: Relevance
“…Daprodustat is a medicine employed to increase erythropoiesis via stabilization of HIF1α. Toth et al (2022) demonstrated that Daprodustat increased aortic calcification in a high phosphate-induced chronic kidney disease mice model. Daprodustat could stabilize HIF1α and HIF2α to accelerate medial calcification, suggesting that there is a possible risk that Daprodustat treatment could accelerate medial calcification in CKD patients with hyperphosphatemia.…”
Section: Vsmcs and Arterial Calcificationmentioning
confidence: 97%
“…Daprodustat is a medicine employed to increase erythropoiesis via stabilization of HIF1α. Toth et al (2022) demonstrated that Daprodustat increased aortic calcification in a high phosphate-induced chronic kidney disease mice model. Daprodustat could stabilize HIF1α and HIF2α to accelerate medial calcification, suggesting that there is a possible risk that Daprodustat treatment could accelerate medial calcification in CKD patients with hyperphosphatemia.…”
Section: Vsmcs and Arterial Calcificationmentioning
confidence: 97%
“…In addition to metabolic aspects, the HIF system is involved in the adaptation to acute and chronic ischemia, atherogenesis, and vascular calcification. However, data from experimental studies are conflicting because they are strongly influenced by the experimental conditions and by the degree of hypoxia of the affected tissues, possibly activating the three HIF and PHD isoforms differently 86 89 …”
Section: Major Adverse Cardiovascular Events and Thrombotic Riskmentioning
confidence: 99%
“…Hypoxia triggers VSMCs calcification and osteogenic differentiation in a HIF-1-dependent and mitochondrial ROSdependent manner (134)(135)(136). As a key effector of hypoxia response, the hypoxia-inducible factor-1α (HIF-1α) can affect the transcription and activity of related metabolic enzymes and regulate the phenotypic transformation of VSMCs.…”
Section: Metabolic Reprogrammingmentioning
confidence: 99%